2022
DOI: 10.1371/journal.pone.0262211
|View full text |Cite
|
Sign up to set email alerts
|

Wading through Molasses: A qualitative examination of the experiences, perceptions, attitudes, and knowledge of Australian medical practitioners regarding medical billing

Abstract: Background Medical billing errors and fraud have been described as one of the last “great unreduced healthcare costs,” with some commentators suggesting measurable average losses from this phenomenon are 7% of total health expenditure. In Australia, it has been estimated that leakage from Medicare caused by non-compliant medical billing may be 10–15% of the scheme’s total cost. Despite a growing body of international research, mostly from the U.S, suggesting that rather than deliberately abusing the health fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Previous research on medical billing in Australia found system issues, rather than intentional abuse by physicians, to be foundational to noncompliant medical billing. 5 Strengths of this research include a large dataset with populationlevel coverage including over 12 000 spinal surgeries over a 9-year period. Limitations were the use of administrative data which does not include specific details about indication or type of surgery, which prevented assessment of some of the issues identified by the MBS Review Taskforce.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research on medical billing in Australia found system issues, rather than intentional abuse by physicians, to be foundational to noncompliant medical billing. 5 Strengths of this research include a large dataset with populationlevel coverage including over 12 000 spinal surgeries over a 9-year period. Limitations were the use of administrative data which does not include specific details about indication or type of surgery, which prevented assessment of some of the issues identified by the MBS Review Taskforce.…”
Section: Discussionmentioning
confidence: 99%
“…These items may have been billed appropriately; however we were not able to assess this as the dataset does not include the indication for surgery. Previous research on medical billing in Australia found system issues, rather than intentional abuse by physicians, to be foundational to non‐compliant medical billing 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to irregular doctor orders, inconsistent expenses and actual time, and poor understanding of pricing policies, billing remains a problem of concern [ 9 ]. Patients doubt their bills, and medical costs are also increasing rapidly [ 5 , 10 ]. In recent years, the National Healthcare Security Administration has increased unannounced inspections, thereby increasing pressure on nurses.…”
Section: Introductionmentioning
confidence: 99%